Assessing the German Act on Corporate Due Diligence Obligations in Supply Chains: a perspective from the smallholder cocoa farmer - Kraft, Sarah Katharina; Quayson, Matthew; Kellner, Florian (Frontiers in Sustainability, 2024)
This research examines the potential outputs, outcomes, and impacts of the German ##R1-01## Act on Corporate Due Diligence Obligations in Supply Chains ##R1-01## (LkSG) on the smallholder cocoa farmers in West Africa. The study primarily relies on a literature review and an impact pathway to conduct a systematic analysis to identify the potential effects of the LkSG on smallholder cocoa farmers. The findings indicate that some, but not all of the risks addressed by the LkSG align with those faced by smallholder cocoa farmers and their families. Additionally, the research also reveals weaknesses, particularly in managing environmental risks, which the LkSG does not adequately cover. Our findings show that in the short-and medium-term, the LkSG has no potential effects on smallholder cocoa farmers. Furthermore, the potential positive impacts of the law on smallholder cocoa farmers will take a long time to realize, as the LkSG considers primarily tier-1 suppliers. Companies in Germany might reassess their supply chains to strive for an LkSG-risk-free supply chain, which could in the long term have sustained impacts on smallholder cocoa farmers. ##R2-01## However, we recommend a comprehensive risk analysis of the cocoa supply chain to enhance the human rights of cocoa farmers ##R2-01##.